Persepsi pegawai sokongan terhadap kepimpinan penyelia di sektor perkhidmatan awam - Mohd Ali, Jamal (Universiti Malaysia Sarawak (UNIMAS), 2005)
The objective of this study is to identify a factor which influences public sector supporting staff's perception on communication, emotion intelligence, personality, work experience, and education level. The study conducted at Road Transport Department, Sarawak. Sample of 100 respondents were involved. Survey forms were used as research instrument to collect feed back from respondent involved This research used survey forms distributed to the respondents for data collection. The gathered quantitative data are then analyzed using Statistical Package For Social Sciences (SPSS) For Windows version 12.0. Results shown there exists a positive relationship between level of communication with supervisor's leadership (r =0.690**, P =0.00), emotion intelligence (r = 0.847**, p =0.00), personality (r 0.757**. p =0.00), experience (r = 0.850**. P = 0.00), and level of education (r = 0.789** P =0.00). Overall, this research indicated that all factor have positive relationship towards supervisor's leadership. Thus, the organization need to give attention to this matter to ensure the organization's objectives is achievable.